2016
DOI: 10.1371/journal.pone.0156040
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Variations of Pine Wood Nematode Bursaphelenchus xylophilus with Different Virulence

Abstract: Bursaphelenchus xylophilus is the causative agent of pine wilt disease which has caused huge economic losses in many countries. It has been reported that two forms of pine wood nematodes existed in its native region, i.e., with strong virulence and weak virulence. However, little is known about the molecular differences between the two forms. To better understand their molecular variations, transcriptome and genome sequences of three strongly virulent and one weakly virulent strains were analyzed. We found 238… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…The unstable expression of ACT has also been confirmed in other species ( Tong et al, 2009 ; Zhu et al, 2013 ; Yan et al, 2014 ). However, a number of previous reports have selected ACT as a reference gene in B. xylophilus ( Qiu et al, 2013 ; Xu et al, 2015 ; Deng et al, 2016 ; Ding et al, 2016 ), and, to the best of our knowledge, no previous studies have systematically examined its expression stability in B. xylophilus . As B. xylophilus is a sister species to B. mucronatus , and morphological and biological characteristics are very similar in the two species ( Mamiya and Enda, 1979 ), B. xylophilus may have arisen from its ancestor B. mucronatus in eastern Asia ( Kanzaki and Futai, 2002 ), and further research is needed to elucidate the expression stability of ACT in B. xylophilus .…”
Section: Discussionmentioning
confidence: 99%
“…The unstable expression of ACT has also been confirmed in other species ( Tong et al, 2009 ; Zhu et al, 2013 ; Yan et al, 2014 ). However, a number of previous reports have selected ACT as a reference gene in B. xylophilus ( Qiu et al, 2013 ; Xu et al, 2015 ; Deng et al, 2016 ; Ding et al, 2016 ), and, to the best of our knowledge, no previous studies have systematically examined its expression stability in B. xylophilus . As B. xylophilus is a sister species to B. mucronatus , and morphological and biological characteristics are very similar in the two species ( Mamiya and Enda, 1979 ), B. xylophilus may have arisen from its ancestor B. mucronatus in eastern Asia ( Kanzaki and Futai, 2002 ), and further research is needed to elucidate the expression stability of ACT in B. xylophilus .…”
Section: Discussionmentioning
confidence: 99%
“…However, virulence is likely to be a complex trait (Semblat et al 2000) and unlikely to be easily linked to single genetic markers (Aikawa et al 2013). For example, Ding et al (2016) identified 117 single nucleotide polymorphic markers (SNPs) linked to virulence in the pine wood nematode Bursaphelenchus xylophilus following genome and transcriptome sequencing of B. xylophilus virulent and avirulent strains. This follows the common application of ITS-RFLP marker (Iwahori et al 1998, Aikawa et al 2003, 2006, which was shown not to be reliable in distinguishing virulence of B. xylophilus strains (Aikawa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More than 3 Mb of genetic variations were investigated as single-nucleotide polymorphisms (SNPs) or small indels between different Japanese B. xylophilus isolates, and the genetic diversity was involved with their virulence and ecological characteristic differences [ 12 ]. Meanwhile, a number of transcripts and exons revealed remarkable differences between the strongly and weakly virulent Chinese B. xylophilus isolates, and functional study of those differences suggested that various virulence B. xylophilus isolates showed differences in their development, propagation, and oxidoreductase activities [ 43 ]. Similarly, there were considerable differences in strongly and weakly virulent isolates of both nematode species.…”
Section: Discussionmentioning
confidence: 99%